Forkhead box O transcription factors as possible mediators in the development of major depression. (December 2015) - Wang, Haitao; Quirion, Rémi; Little, Peter J.; Cheng, Yufang; Feng, Zhong-Ping; Sun, Hong-Shuo; Xu, Jiangping; Zheng, Wenhua
Abstract: Forkhead box O (FoxO) transcription factors play important roles in cellular physiology and biology. Recent findings indicate that FoxOs are also involved in the development of major depressive disorder. Alterations in the upstream molecules of FoxOs, such as brain derived neurotrophic factor or protein kinase B, have been linked to depression. Antidepressants, such as imipramine and venlafaxine, modify the FoxOs phosphorylation. Furthermore, FoxOs could be regulated by serotonin and norepinephrine receptor signaling as well as the hypothalamic–pituitary–adrenal axis, all of which are involved in the pathogenesis of depression. FoxOs also regulate neuronal morphology, synaptogenesis and adult hippocampal neurogenesis, which are viewed as candidate mechanisms for the etiology of depression. In this review, we emphasize the possible roles of FoxOs during the development of depression and make some strategic recommendations for future research. We propose that FoxOs and its signaling pathways may constitute potential therapeutic targets in the treatment of depression. Highlights: FoxO transcription factors regulate the behavioral manifestation of depression. Antidepressants regulate the phosphorylation/activities of FoxOs. FoxOs are regulated by serotonin and norepinephrine receptor signaling and HPA axis. FoxOs induce cell atrophy and this effect may affect neuronal morphology.